2021
DOI: 10.1108/tqm-02-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Addressing strategic human resource management practices for TQM: the case of an Indian tire manufacturing company

Abstract: PurposeThis study aims to identify SHRM (strategic human resource management) essential practices for the TQM (total quality management) program regarding an Indian tire manufacturing company and formulate an inclusive interrelationship to prioritize them.Design/methodology/approachSemistructured interview with ten experts from the company was made to give SHRM practices scores. The SLR (systematic literature review) and TOPSIS (technique for order of preference by similarity to ideal solution) techniques are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 135 publications
(171 reference statements)
0
28
0
Order By: Relevance
“…While all the articles in this special issue partially recognize the importance of re-contextualization as suggested by Donnelly and Johns (2021), one of the articles by Ahmad et al and another by Sampat et al proposed a framework specifically to address this gap by proposing fresh WFH frameworks. Another article by Tran et al took on the challenge posed by Verma et al . (2022) of linking TQM with strategic HRM by integrating Quality 4.0 and COVID-19 characteristics and other relevant frameworks.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While all the articles in this special issue partially recognize the importance of re-contextualization as suggested by Donnelly and Johns (2021), one of the articles by Ahmad et al and another by Sampat et al proposed a framework specifically to address this gap by proposing fresh WFH frameworks. Another article by Tran et al took on the challenge posed by Verma et al . (2022) of linking TQM with strategic HRM by integrating Quality 4.0 and COVID-19 characteristics and other relevant frameworks.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Scholars including Petani and Mengis (2021) also advise on studying the individuals' affective development in light of the increased use of information technologyenabled spaces as has the potential to enhance our existing knowledge on emotionally engaging employees in a better way. In a bid to capture the quality of the rapidly changing work environment, Verma et al (2022) suggested to establish a link between total quality management and strategic HRM. The aforementioned literature suggests that there is a difference between traditional working from office and WFA and it requires scholars to re-examine the existing theories.…”
mentioning
confidence: 99%
“…, 2020). TOPSIS methodology is commonly used to solve decision-making problems and it is based on the deliberation that the best-selected solution is to close the ideal solution and far from the anti-ideal solution (Verma et al ., 2022a b). Moreover, it is based on a comparison between all the alternatives included in the problems and used large-scale decision-making problems.…”
Section: Methodsmentioning
confidence: 99%
“…The framework was developed by Kunz and Gold (2017) by merging literature from the disciplines of sustainable and humanitarian SCM while Jauhar et al. (2021) focused on supplier selection for sustainable operations in the manufacturing company and Verma et al . (2022a, b) measured sustainability barriers toward operative Industry 4.0 in digital manufacturing.…”
Section: Literature Review Regarding the Current Inquiry A Survey Of ...mentioning
confidence: 99%
“…In specific, their role in the TQM system revolves around assuming responsibilities for quality, evaluating quality performance, improving quality, setting goals and making quality planning (Kaynak, 2003). In addition, scholars have agreed that leadership is a foundational element of the TQM system that is required to support internal and external partners and processes to improve quality performance, and consequently, improve operational performance and organizational performance, and innovativeness (Kaynak, 2003;Sharma, 2017a, b, 2018;Verma et al, 2021). Thus, leadership, in particular total quality leadership, becomes a competitive advantage to the organizations (Powell, 1995;Chen et al, 2020).…”
Section: Literature Review 21 Total Quality Leadershipmentioning
confidence: 99%